Toward the Consolidation of a Sociology of Classroom Assessment: A Narrative Review of the French-Language Literature - Adriana Morales-Perlaza; Joëlle Morrissette (ADMEE-Canada, 2020)
In this article, we propose a consolidation in the field of sociology of classroom assessment, continuing the efforts made in this direction in the 1990s. Updating this field is crucial in order to better understand, among other things, the changes that have occurred in student learning assessment practices following the implementation of the New Public Management. We offer a literature review of 59 French-language articles closely related to the sociology of classroom assessment. Our analysis highlights four categories of sociological issues arising from this literature: 1) the instructive function of assessment and progression of learning; 2) the assessment of ability to act and adaptation to complex contexts; 3) external and standardized assessment and producing measurable results; and 4) assessment as the manifestation of norms of excellence and the democratization of schooling success. We conclude with a presentation of research perspectives that would promote the consolidation of this field.